2007 IEEE Symposium on VLSI Circuits 2007
DOI: 10.1109/vlsic.2007.4342779
|View full text |Cite
|
Sign up to set email alerts
|

AC Power Supply Circuits for Energy Harvesting

Abstract: Passive energy harvesting from mechanical vibration has wide application in wearable and embedded sensors to complement or replace batteries. Energy harvesting efficiency can be increased by eliminating AC/DC conversion. A test chip demonstrating self-timing, power-on-reset circuitry, and memory for energy harvesting AC voltages has been designed in 180 nm CMOS and tested. Circuit operation is confirmed for supply frequencies between 60 Hz and 1 kHz with power consumption below 130 µW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…Figure 5 shows the block diagram of a test chip developed to explore circuit design for energy harvesting AC power supplies [9]. The chip combines a novel power-on-reset (POR) circuit, self-timed circuit design, and dynamic memory to implement an energy-scalable programmable digital FIR filter based on Distributed Arithmetic [10].…”
Section: Digital Circuits and Microarchitecturementioning
confidence: 99%
“…Therefore we will use the digital energy/bit from Section IV, the power conversion efficiencies from Section III, and the 90nm CMOS integrated solar power generation from Section II, to estimate the minimum surface area and volume of an energy harvesting sensor system. Assuming we want to compute 16 bit results at 1MHz using the microarchitecture of [9], and 76.3% DC/DC conversion efficiency, the system would require 9763 µm 2 of solar diode area. Using vibration energy scavenging, assuming the maximum energy density, and 100% efficiency with an AC supply-tolerant digital circuit, the system would require 30.2mm…”
Section: Digital Circuits and Microarchitecturementioning
confidence: 99%
“…Although asynchronous circuits, with large tolerances for process, voltage, and temperature variations, could be considered previous work for AC supplies, they typically do not take into account deliberately time-varying voltages with wide swings [Spars 2001]. Recent work has investigated the use of asynchronous logic in subthreshold operation [Lotze et al 2001], but because an AC supply can dip below the usable voltage level at any time, requiring a quick power-on when proper levels are restored for brief periods of time [Wenck et al 2007], asynchronous circuits are a possible starting point, but not necessarily a full solution to the AC supply problem.…”
Section: Introductionmentioning
confidence: 99%